Cidades Invisíveis. Fotografia como processo de desalienação para a compreensão da arquitectura e do meio urbano
The technological vertigo of communication advocates a picture of visual swelling that outlines a dichotomy of contemporaneity: the imagetic ecstasy provides us with the gift of ubiquity and excessive sharpness, while sterilizing our presence in the spaces, and thus our perceptions. With that, from a perspective of the areas of Architecture and Photography, this Dissertation traces relations between the problematic and the disciplines in question, seeking to clarify the reflections of the emphasized framework in the architectural and urban productions and reproductions, as well as in the relation between the subject and its habitat.Resorting to the bases of a theoretical-referential investigation, a visual narrative is built, which takes shape as a zine, structured from the collage strategy, shaping a response to the collapse of the articulations between fabric, structure and individual, supported on the paradox of the image.